Population Indicator’s Ranks in Qassim Region, A Comparative Study with Saudi Regions According to 2022 Census - Abbakar, Mustafa Mohamed Ali (Dirasat: Human and Social Sciences, 2025)
Objectives: The study aims to address demographic situation in a geographical region, which is the Al-Qassim region, one of the administrative regions in the Kingdom of Saudi Arabia, by examining some demographic variables according to the actual population census conducted by the Saudi General Authority for Statistics in the year 2022. These variables include population sizes in areas, growth, density, gender, and age groups. Method: The researcher adopted the regional geographical approach to understand the regionalism of the study area and to discern the influential spatial relationships. Additionally, the analytical statistical methodology was necessary to analyze the variables and process their numbers, using tools such as maps, reports, various charts relying on Excel 2016 program, statistical tables, and data from the Saudi General Authority for Statistics and its scheduled reports. Results: The study’s findings revealed that the Al-Qassim region holds a moderate position in its population indicators among Saudi regions in most demographic variables, based on its natural geographical conditions that accommodate the population situation. Eight demographic indicators out of thirteen were in the middle range of the numbers, such as general size, Saudi and resident populations, and overall growth. Conclusion: The study recommended focusing on utilizing agricultural resources to stabilize the population and enhance internal transportation in the region and beyond, as well as enhancing economic sectors as factors attracting population. It also pointed out areas of population that need to be studied.